Effect of a single cold stress exposure on the reproductive behavior of male crickets. (August 2021) - Chipchase, Kathryn M.; Enders, Alexa M.; Jacobs, Elizabeth G.; Hughes, Michael R.; Killian, Kathleen A.
Graphical abstract: Highlights: Male crickets exposed to 0 °C for 6 h were less likely to carry a spermatophore. Female contact could induce cold stressed males to produce a spermatophore. Cold stressed males had difficulty transferring the spermatophore to a female. Cold stressed males that successfully mated sired as many offspring as controls. Abstract: Cold stress is an important abiotic factor that can impact insect physiology, behavior, and overall fitness. Upon exposure to cold temperature, many insects enter a reversible state of immobility called chill coma. If the cold stress is brief and mild enough, insects can recover and regain full mobility upon return to warmer temperatures. However, the long-term impact of sublethal cold stress on insect behavior has been understudied. Here, sexually naïve adult male Acheta domesticus crickets were exposed to a single 0 °C cold stress for 6 h. One week later, the ability of these males to mate with a female was examined. For mating trials, a cold stressed male cricket was paired with a non-cold stressed, control female. Control pairs were comprised of a non-cold stressed control male and control female. Cold exposed males were less successful at mating than control males because most did not carry a spermatophore at the time of their mating trials. However, when these cold stressed males were allowed 1 h of chemosensory contact with a female, most produced a spermatophore. Males that produced spermatophores were given the opportunity to mate once with a female, and stressed males that successfully mated sired as many offspring as did control males. However, our results support that a single cold stress exposure can negatively impact the reproductive fitness of male crickets since it reduced their capacity to carry spermatophores and, as a consequence, to attract females.